(untitled) (International Seven Journal of Health Research, 2023)
On January 30, 2020, the World Health Organization (WHO) declared a Public Health Emergency of International Concern, due to the novel coronavirus 2019 (definitively named on February 12, 2020 as COVID-19). Initially, Covid-19 infection did not appear to affect the paediatric population, with few reported cases, negligible morbidity, and mortality, and generally asymptomatic. However, subsequently, the English National Health System (NHS) issued an alert about new clinical manifestations of COVID-19 in children, which may be temporarily linked to a previous SARS-CoV-2 infection and determined by history of exposure, serology, or viral detection by RT-PCR, described as a paediatric multisystem inflammatory syndrome temporally associated with SARS-COV-2 (MIS-C). This paper reports the case of a 3-year-old and 6-month-old male patient, neuropathic, microcephalic, epileptic who sought medical attention with persistent fever and abdominal pain. Laboratory tests showed myositis, hepatitis, pancreatitis, positive PCR, elevated D-dimer and serology for covid-19 with non-reactive IgM and reactive IgG, thus meeting the diagnostic criteria for MIS-C. As for its prognosis, MIS-C is a dangerous and potentially fatal disease. The estimated mortality rate for MIS-C is between 0% and 5.3%, which is considered low but much higher than the overall mortality rate for children with COVID-19 (0.09%). Treatment depends on the severity of the disease, the risk of complications, and the possibility of follow-up, with most patients requiring hospitalization.